First Record of Trichodina magna Van As and Basson, 1989 (Ciliophora: Trichodinidae) from Gills of Blue Tilapia Oreochromis aureus (Steindachner, 1864) in Iraq - Abdul-Ameer, Kefah Naser; Atwan, Fatima Khalaf (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The Ciliophoran Trichodina magna Van As and Basson, 1989 is recorded for the first time in in Iraq from gills of the blue tilapia Oreochromis aureus (Steindachner, 1864) Iraq from Al-Graiat location on the Tigris River at Baghdad city. The description and measurements of this external parasite as well as its illustrations are given.